Analisis Pengungkapan Corporate Social Responsibility Bank Syariah di Indonesia Berdasarkan Islamic Sosial Reporting Index - Malikhatun, Irna; Rahmawati, Rafika (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) for IslamicCommercial Banks using the Islamic Social Reporting Index (ISR) method. The research period usedis 2016-2019. This study uses a quantitative approach. The research population includes all IslamicCommercial Banks (BUS) that publish Annual Reports on their respective websites during the 2016-2019 period. The sample was determined by purposive sampling and obtained 13 Islamic CommercialBanks. The results of this study indicate that of the 13 Islamic Commercial Banks disclosed during2016-2019 that each bank has a different level of disclosure. Bank Mumalat Indonesia and BankSyariah Mandiri received the title Very Informative while Bank Panin Dubai Syariah, Bank AcehSyariah, BNI Syariah, BRI Syariah, BCA Syariah, Mega Syariah, BJB Syariah produced Informativepredicate. Meanwhile, BTPN Syariah, Bukopin Syariah, Bank Net Syariah and Bank Victoria Syariahreceived the title of Less Informative.